Wire texture C-axis distribution of strontium ferrite/PA-12 extruded filament - Gabriela Espinosa-Rodriguez; Oluwasola Arigbabowo; Jonathan Alvarado; Jitendra Tate; Wilhelmus J. Geerts (AIP Advances, 2024)
The magnetic anisotropy of strontium ferrite (SF)/PA12 filament, a popular hard magnetic ferrimagnetic composites that is used for 3D-printing of permanent magnets, is studied by vibrating sample magnetometry. The studied filaments have a composition of SF/PA-12 thermoplastic composite with a 40% wt.  ratio of SF. SF particles are non-spherical platelets with an average diameter of 1.3 um and a diameter to thickness ratio of 3. Filaments are produced by a twin-screw extruder and have a diameter of 1.5 mm. SEM images show that the SF particles are homogeneously distributed through the filament. VSM measurements on different parts of the filaments show that the outer part of the cylindrical filament has a higher anisotropy, and the core is mostly isotropic. This conclusion is consistent with computational work by others which suggest that particle alignment predominantly takes place near the walls of the extruder die where shear flow is maximum. Additional hysteresis curve measurement of the outer cylindrical part of the filament parallel to the r and ϕ directions indicates that the squareness of the hysteresis curve (S) is larger in the r-direction. This indicates that the outer surface of the filament has a strong easy axis in the r-direction. We conclude that the SF platelets line up parallel to the walls of the extrusion die.